Tubulin polymerization promoting protein family member 3 (TPPP3) overexpression inhibits cell proliferation and invasion in nasopharyngeal carcinoma. Issue 1 (1st January 2021) - Su, Qisheng; Yang, Zheng; Guo, Xiaobin; Mo, Wuning; Li, Xiaohong
ABSTRACT: The function of tubulin polymerization promoting protein family member 3 (TPPP3) in tumor cells is complicated, and the role of TPPP3 in nasopharyngeal carcinoma (NPC) remains unclear. This study aims to explore the expression of TPPP3 in NPC and its effect on NPC cells. The expression of TPPP3 in NPC tissues and other cancers were analyzed by using the Oncomine and Gene Expression Omnibus (GEO) databases. The mRNA and protein of TPPP3 were detected in NPC tissues by quantitative real-time PCR and immunohistochemistry. Furthermore, TPPP3 was overexpressed in 5–8 F and HONE1 cell lines by lentivirus transfection, and functional analysis of TPPP3 in NPC was evaluated through in vitro experiments. The expression of TPPP3 was significantly down-regulated in NPC tissues and cells. Overexpression of TPPP3 significantly inhibited proliferation of 5–8 F and HONE1 cells in vitro. In addition, overexpression of TPPP3 significantly attenuated the invasion ability of 5–8 F, HONE1 cells in vitro, but have no significant effect on migration ability. Furthermore, TPPP3 overexpression diminished the expression of MMP-2 and MMP-9 mRNA. By analyzing dataset GSE12452, it was interesting that TPPP3 high expression group mainly functioned in B cell receptor signaling pathway, cell cycle and DNA replication. In conclusion, our results suggest that TPPP3 may be considered as an antioncogene, which plays an important role in the occurrence and progression of NPC. Abbreviations: TPPP3: tubulin polymerization promoting protein family member 3; NPC: nasopharyngeal carcinoma; GEO: Gene Expression Omnibus; qRT-PCR: quantitative real-time PCR; GFP: green fluorescence protein; MOI, transfected multiplicity of infection; CCK-8: cell counting kit-8; OD: optical density; GSEA: gene set enrichment analysis; GO: Gene Ontology; KEGG: Kyoto Encyclopedia of Genes and Genomes; MMP-2: matrix metalloproteinase-2; MMP-9: matrix metalloproteinase-9.